PENGARUH STRATEGIC ORIENTATION, GOVERMENT REGULATION, DAN REVERSE LOGISTICS TERHADAP GREEN SUPPLY CHAIN MANAGEMENT PADA PT XYZ - Aditya, Kelvin Syahrul; Alhazami, Lutfi (Lembaga Pengembangan Kinerja Dosen, 2023)
Companies are required to apply the concept of green supply chain management to minimize environmental pollution which is increasingly polluted. This study aims to determine the influence of strategic orientation, government regulation and reverse logistics on green supply chain management at PT XYZ as one of the companies that applies the concepts of strategic orientation, government regulation and reverse logistics in its production process. This study was conducted with a quantitative approach and associative research design with a sample of 127 respondents. The instrument used by researchers is a questionnaire. Quality testing on research instruments is a test of validity and reliability. Data analysis uses descriptive analysis, while for hypothesis testing using multiple linear regression. The results of this study explain that there is a positive and significant relationship between strategic orientation, government regulation and reverse logistics towards green supply chain management with a correlation coefficient value. This analysis was only conducted on one company and did not take into account other variables or moderator variables that affect green supply chain management.